Assessment and Treatment of Concussion in the Pediatric Population - Lugo, Giancarlo J.; Beletanga, Maria; Goldstein, Laura; Rana, Mandeep; Jonas, Rinat; Torres, Alcy R. (Seminars in Neurology, 2021)
Traumatic brain injury (TBI) is common in children. The evaluation and management of children with TBI is based on the research performed in adults. There is a relative paucity of research in the literature involving children and many of the practice recommendations for this age are based on expert opinion in the absence of good research studies in both sports and non–sports-related injuries. The pediatric population is heterogeneous and the approach might be specific for infants, preschoolers, school age children, and adolescents. Children may also suffer from neurodevelopmental disabilities, making their evaluation even more challenging. Adult neurologists are often asked to see children due to increasing demands. This review will focus on specific issues related to TBI in children that might be useful to adult neurologists. Science, however, is evolving rapidly and physicians should make sure to remain up to date to offer evidence-based services to their patients.
Keywords: traumatic brain injury; concussion; children